Progressive macular hypomelanosis among Egyptian patients: a clinicopathological study - Mohamed Khaled Selim; El-Shahat Farag Ahmed; Mamdouh Morsy Abdelgawad; Mohammed Fawzy El-Kamel (Mattioli1885, 2011)
Background: Progressive macular hypomelanosis (PMH) is a disease of unclear etiology. Propionbacterium acnes (P. acnes) was claimed to be an etiological factor. Objectives: The purpose of this study was to document the clinicopathological features of PMH in Egyptian patients and to evaluate the therapeutic outcome. Methods: Patients with clinical features of PMH were recruited. Wood's lamp examination, skin scrapings for fungi, and skin biopsy specimens were obtained. Biopsies were stained with hematoxylin and eosin, PAS, Fontana-Masson, and S100 protein. Patients received either narrow-band UVB (nbUVB) or nbUVB plus daily topical clindamycin 1% and benzoyl peroxide gel 5% (bcUVB). The period of active treatment was 14 weeks followed by a follow-up period of 24 weeks. Results: Twenty-nine patients were included. Microscopic evaluation of skin biopsy specimens showed no significant differences between lesional and normal skin. Fontana-Masson stained sections showed overall reduction of melanin granules in the basal layer of lesional skin only and S100 staining did not detect significant differences in the number of melanocytes in lesional and normal skin. Nearly complete repigmentation was reported in 10 patients treated with bcUVB compared to 9 patients treated with nbUVb with no significant differences between both groups after 14 weeks. Only 2 patients in each group retained the pigmentation and the remaining patients returned to the baseline color before treatment. Conclusions: This study documented the clinicopathological features of PMH among Egyptians. No permanently effective treatment is available. Further studies are needed to prove or disprove the pathogenic role of P. acnes in PMH.